Progesterone: Its occurrence in plants and involvement in plant growth - Iino, Mayumi; Nomura, Takahito; Tamaki, Yuji; Yamada, Yumiko; Yoneyama, Koichi; Takeuchi, Yasutomo; Mori, Masaki; Asami, Tadao; Nakano, Takeshi; Yokota, Takao (Phytochemistry (Oxford), 2007)
Progesterone was identified from a variety of plants, while several genes encoding putative progesterone-binding proteins were found to be expressed in various tissues of Arabidopsis thaliana and rice. Furthermore, progesterone affected plant growth in some biological systems. These findings suggest that progesterone may be involved in plant growth. Progesterone is a mammalian gonadal hormone. In the current study, we identified and quantified progesterone in a range of higher plants by using GC–MS and examined its effects on the vegetative growth of plants. The growth of Arabidopsis ( Arabidopsis thaliana) seedlings was promoted by progesterone at low concentrations but suppressed at higher concentrations under both light and dark growth conditions. The growth of the gibberellin-deficient mutant lh of pea ( Pisum sativum) was also promoted by progesterone. An earlier study demonstrated that progesterone binds to MEMBRANE STEROID BINDING PROTEIN 1 (MSBP1) of Arabidopsis. In this work, we cloned the homologous genes of Arabidopsis, MSBP2 and STEROID BINDING PROTEIN ( SBP), as well as of rice ( Oryza sativa), OsMSBP1, OsMSBP2 and OsSBP and examined their expression in plant tissues. All of these genes, except OsMSBP1, were expressed abundantly in plant tissues. The roles of progesterone in plant growth were also discussed.